Salici's Puppets, Hall of Western States
The Golden Gate International Expositionis proud to have these famous Puppets on Treasure Island as one of the most outstanding attractions at the Fair in '40. Salici Puppets are no ordinary marionetters, but for six generations undisputed masters of the ancient art of Puppetry entertainment. They Sing, Dance, Smoke, do Acrobatic Stunts, and act like Human Beings. Some critics have said: "Preferrable to artists of Flesh and Blood!"